Lithium-Irradiated Poly(vinylidene fluoride) Nanohybrid Membrane for Radionuclide Waste Management and Tracing - Prakash O.; Mhatre A.M.; Tripathi R.; Pandey A.K.; Yadav P.K.; Khan S.A.; Maiti P. (My University, 2025)
The conducting nanochannel is made up of poly(vinylidene fluoride) and its nanohybrid (NH) membrane through irradiation of high-energy (80 MeV) lithium ions followed by chemical etching. The NH is prepared through the solution route by dispersing 2-D-layered silicates in a polymer matrix. Morphological studies indicate that the dimension of the conducting nanochannel is in the range of 40-50 nm. The nanochannels are filled with the styrene monomer and are polymerized within the channels to use the free radicals available in the periphery of the walls, exposed after etching the irradiated films. Polystyrene chains are sulfonated and, thereby, converted the nanochannel ion conduction exclusively with a proton conduction of 30 mS·cm-1 in the NH membrane. The effect of fluence has been evaluated for the improvement of different useful parameters of the membrane. Structural alteration of the functionalized membrane is revealed through XRD, thermal measurements, and morphological studies. The functionalized membranes are used to capture radionuclide 241Am3+, an alpha emitter. The studies on uptake kinetics show more than ∼98% uptake within an hour. Alpha radiography is carried out to map the radionuclide distribution in the nanochannels. A comparison of Li+- and Ag+-ion-irradiated films indicates preferential grafting at the near-surface of the membrane in the case of Ag+-ion-irradiated films, whereas comparatively more uniform distribution of radionuclides is observed in the Li+-irradiated membrane across the depth. Measurement of scintillation pulse height spectra suggests relative response of the membrane depending on the nanochannel dimension. However, Li+-ion-irradiated films are better suited for the possible application in uptake/transport of radionuclides, whereas Ag+-ion-irradiated films are better suited for their applications in radionuclide sensing. ©